2002
DOI: 10.1097/00001888-200210000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Care Outcomes by Teaching Quality Improvement to Medical Students in Community-based Practices

Abstract: Medical student-driven CQI projects can improve the quality of care for diabetes at practices in which the students participate while introducing them and their preceptors to the process of quality measurement and improvement. Formative input from students should be used to optimize CQI experiences. Using medical students to lead CQI efforts in private practices may represent an underutilized resource to improve the care of patients in community-based practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 3 publications
2
60
0
Order By: Relevance
“…14,17 In contrast to our study, which did not affect intermediate clinical outcomes, these interventions included additional educational components such as readings in quality of care, self-reflection, commitment to change surveys, and learner involvement in quality improvement processes. Whereas this suggests that multifaceted interventions may be beneficial, a systematic review of 85 audit and feedback studies did not find evidence that multifaceted interventions were more effective than audit and feedback alone.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…14,17 In contrast to our study, which did not affect intermediate clinical outcomes, these interventions included additional educational components such as readings in quality of care, self-reflection, commitment to change surveys, and learner involvement in quality improvement processes. Whereas this suggests that multifaceted interventions may be beneficial, a systematic review of 85 audit and feedback studies did not find evidence that multifaceted interventions were more effective than audit and feedback alone.…”
Section: Discussionmentioning
confidence: 87%
“…6,[14][15][16][17][18] One randomized controlled trial using chart audit of 10-12 patients per resident, report cards assessing 78 audit items, and a 10-to 15-minute feedback session did not demonstrate improved patient management. 19 Possible reasons for the lack of benefit with this approach include the limited number of patients assessed per resident; diffuse nature of the feedback; and the single, brief feedback session.…”
Section: Discussionmentioning
confidence: 96%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] Several of these studies have shown an improvement in patient care as measured by specific quality indicators. The I 3 POP takes a broader approach and incorporates the triple aim for both learners and faculty development.…”
Section: Discussionmentioning
confidence: 99%
“…5 Medical students are an undervalued resource in health care organizations, and when educational providers such as the IHI Open School provide medical students with the skills and knowledge to lead improvement, they can lead change in health care. 10,22,23 Implications for Practice, Policy, and Education and Further Work Needed…”
Section: Relationship With the Literaturementioning
confidence: 99%